2012
DOI: 10.1111/j.1600-051x.2012.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and periodontal disease in young adults: a population‐based birth cohort

Abstract: AimTo evaluate the association between obesity and periodontal disease and the mediating effect of oral hygiene, systemic inflammation and carbohydrate intake.Material and methodsSubjects born in 1982 in Pelotas, Brazil (n = 5,914), have been followed for several times. Oral health was assessed in a representative sample of 720 individuals at 24 years. Obesity, waist circumference and number of episodes with obesity between 15 and 23 years of age were the main exposures. Mediating effect of oral hygiene, C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 32 publications
9
38
0
12
Order By: Relevance
“…11,13,14,[17][18][19][20] Some studies were conducted on large and more representative cohorts but still with diverse methodology, particularly relating to the diagnosis of PD, and were restricted to certain sex or age strata. 5,12,15,21 Very few studies other than ours have considered oral health or hygiene status in their analyses. 12,17 One of these was a Brazilian population-based birth cohort with a representative sample of 720 subjects in which the association between periodontal disease was determined through oral examination (at the age of 24 years) and obesity was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,14,[17][18][19][20] Some studies were conducted on large and more representative cohorts but still with diverse methodology, particularly relating to the diagnosis of PD, and were restricted to certain sex or age strata. 5,12,15,21 Very few studies other than ours have considered oral health or hygiene status in their analyses. 12,17 One of these was a Brazilian population-based birth cohort with a representative sample of 720 subjects in which the association between periodontal disease was determined through oral examination (at the age of 24 years) and obesity was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, it is not totally clear what the causal pathway between PD and CVD risk is. 10 Many observational studies have evaluated the association between different levels of periodontal disease and traditional CVRFs, such as obesity or correlated measurements, [11][12][13][14][15][16][17][18][19][20][21] while others have reported some association with diabetes 22 or metabolic disorders. 23,24 Among these studies, most reported an increased odds ratio (OR) for the relationship between obesity and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested a correlation between obesity and chronic periodontitis (2)(3)(4)(5)(6)(7)(8)(9). In addition, clinical periodontal parameters, such as gingival inflammation and loss of attachment, are associated with a high body mass index (BMI) and waist-to-hip ratio (WHR) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…O acúmulo de placa bacteriana nas superfícies dentárias está associado com a presença de alterações bucais como a presença de sangramento gengival e de cálculo dentário, e consequentemente à doença periodontal (IRIGOYEN-CAMACHO et al, 2014;FRANCHINI et al, 2011). Os obesos avaliados neste estudo (G1 e G2) apresentaram pobres condições de higiene bucal na avaliação inicial (Tabela 4), dado que vai ao encontro do exposto na literatura científica (KIM et al, 2014;AKMAN et al, 2012;DE CASTILHOS et al, 2012;MATHUR et al, 2011;ZERMENO-IBARRA et al, 2010).…”
Section: Condições Periodontais E De Higiene Bucalunclassified
“…Em um estudo de coorte prospectiva, a inflamação sistêmica e a pobre condição de higiene bucal dos indivíduos foram descritas como mediadoras da associação entre a obesidade e a gengivite (DE CASTILHOS et al, 2012). Hábitos bucais deletérios como o tabagismo podem contribuir para o estabelecimento e progressão das alterações periodontais (TONETTI et al, 2015), bem como o consumo frequente de bebidas alcoólicas, que pode ser exacerbado após a Cirurgia Bariátrica, contribuindo para o reganho de peso (ODOM et al, 2010).…”
Section: Condições Periodontais E De Higiene Bucalunclassified